Analisis Faktor Kepercayaan dan Kemudahan Penggunaan yang Mempengaruhi Minat UMKM pada Desa Telaga Jernih dalam Menggunakan QRIS Sebagai Alat Pembayaran - Dina Cheetah Khairiyah; Haura Afnani Zanjabila; Julia Hamdini Nasution; Siti Nur Aisah Sitompul; M. Amar Adly (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the influence of trust and ease of use on the interest of MSMEs in Telaga Jernih Village in adopting QRIS (Quick Response Code Indonesian Standard) as a digital payment tool. In the era of rapid economic digitalization, QRIS facilitates non-cash transactions while increasing trust and efficiency in business management. The research method used a literature study and the implementation of Community Service Program (KKN) involving socialization and mentoring on the use of QRIS and Google Maps as MSME promotional tools. The results show that MSMEs are beginning to understand the benefits of digital technology in increasing the effectiveness and competitiveness of their businesses. Trust in system security and ease of use are the main factors in increasing interest in QRIS adoption among MSMEs in the village. This study provides implications for stakeholders to support the digital transformation of MSMEs through continuous training and socialization.